Facilitators and Barriers of Adherence to Nutrition Counseling Sessions of Patients with Type 2 Diabetes at Nakuru County Referral and Teaching Hospital - Alungata, Josephine; Chege, Peter; Mokaya, Moses (Kabarak University, 2025)
Abstract The prevalence of diabetes is rapidly increasing, making it a major global health concern. Nutrition counseling sessions are essential for promoting healthy eating habits and dietary choices among patients with type 2 diabetes. However, adherence to these sessions remains low in Kenya. This study examined facilitators and barriers to nutrition counseling session adherence among patients with type 2 diabetes at Nakuru County Referral and Teaching Hospital. A mixed-method explanatory sequential design involved 396 patients and 4 healthcare providers. Participants were selected through probability and purposive sampling. Data collection combined cross-sectional and phenomenological approaches using questionnaires, in-depth interviews, and key informant interviews. Quantitative data were analyzed using SPSS (Version 26) for descriptive statistics, chi-square tests, and logistic regression, while qualitative data were analyzed through inductive thematic analysis. A total of 392 patients aged 51–70 years participated in the quantitative phase, and 40 patients in the qualitative in-depth interviews. Adherence to nutrition counseling sessions, defined by attending more than three sessions per year, was low, with 45.2% not attending any session in the past six months and 32.7% attending only once. Sociodemographic factors showed no significant associations with session adherence (p > 0.05), while health-related factors such as diabetic complications (p = 0.036) and regular clinic attendance (p = 0.001) were significant predictors. Key facilitators included positive perceptions of sessions, supportive healthcare providers, and family support, while barriers were financial constraints, comprehension issues, and logistical challenges. Health-related factors and regular clinic attendance significantly predict nutrition counseling session adherence, suggesting areas for intervention.
Full text
Keywords: Barriers; Facilitators; Nutrition Counseling Sessions; Adherence; Type 2 Diabetes